2020
DOI: 10.1007/s11356-020-08757-6
|View full text |Cite
|
Sign up to set email alerts
|

Climate disturbance impact assessment in West Africa: evidence from field survey and satellite imagery analysis

Abstract: Extreme drought events from climate disturbances are weakening livelihood and limiting agriculture and livestock production in the Sahel region. The lack of relevant information to anticipate coping measures has exacerbated impacts leading to climate adaptation failure in most parts. In this regard, the current research paper has collected important datasets with an objective to assess the impact of extreme drought events on household's livelihoods for better understanding impacts, local people's perception, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…There is an abundance of evidence on the regional, national, and global scale that environmental problems and climate changes have detrimental effects on agricultural production (Tesfahunegn and Gebru 2019). Also, many studies have confirmed the significant impact of CO 2 emissions on agricultural output (Traore et al 2020). Climate change might have direct (e.g., temperature increase and change in rainfall patterns) and indirect effects (e.g., growth of diseases that cause higher costs and make crop management more difficult) (Qureshi et al 2016;Zaied and Cheikh 2015) on agricultural production.…”
Section: Area Productionmentioning
confidence: 99%
“…There is an abundance of evidence on the regional, national, and global scale that environmental problems and climate changes have detrimental effects on agricultural production (Tesfahunegn and Gebru 2019). Also, many studies have confirmed the significant impact of CO 2 emissions on agricultural output (Traore et al 2020). Climate change might have direct (e.g., temperature increase and change in rainfall patterns) and indirect effects (e.g., growth of diseases that cause higher costs and make crop management more difficult) (Qureshi et al 2016;Zaied and Cheikh 2015) on agricultural production.…”
Section: Area Productionmentioning
confidence: 99%
“…Although climate change is expected to have major impacts on a global scale, the rural population in the tropics is more vulnerable to climate change (IPCC, 2007, 2014). Some of the impacts of climate change include increased morbidity and mortality (Gasparrini et al , 2017), decreased labour productivity and supply, decreased economic output (Wossen et al , 2018), mass migration (Hsiang and Sobel, 2016), lower human capital (Garg et al , 2018), reduced working hours (Masuda et al , 2019) and extreme climate events (IPCC, 2014; Traore et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Africa has been experiencing extreme climate events and would, therefore, need external support to reduce its possible devastating effects in the future (New et al , 2006; Niang et al , 2014; Traore et al , 2020). Agriculture in Africa uses 65% of the labour force and contributes 32% to the gross domestic product (GDP) of the continent (Chauvin et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Drought is the major climate constraint negatively affecting local community in the semi-arid zone of Burkina Faso [6], and yield deficit is caused by a decrease of rainfalls [7,8]. In this country, the rainfed agriculture is subjected to climate variability, and recurrent droughts spells have become the most important threat to ensuring food security [9].…”
Section: Introductionmentioning
confidence: 99%